Indoor air quality and prevalence of sick building syndrome among office workers in two different offices in Selangor - Zamani, Mohd Ezman; Jalaludin, Juliana; Shaharon, Mohd Nafiz (Science Publications, 2013)
This study was done to investigate the relationship between Indoor Air Quality (IAQ) and prevalence of Sick Building Syndrome (SBS) in two different offices (old and new) in Selangor. Hundred and seventy workers were selected consist of 85 office workers for each building. Questionnaire based on Indoor Air Quality and Work Symptoms Survey, NIOSH, Indoor Environmental Quality Survey, 1991 was used to record prevalence of SBS. Measurement of indoor air quality was performed using instruments recommended by IAQ Code of Practice, Department of Occupational Safety and Health, Malaysia. IAQ supplied air was significantly higher in new building with the median 22.49 cfm/person while 15.79 cfm/person in old building (z = -6.23, p<0.001). The prevalence of SBS in old building was significantly higher compared to the new building (χ2 = 30.6, p<0.001). Levels of indoor air pollutants in old building were significantly higher compared to new building for: CO2 (z = -4.62, p<0.001); TVOC (z = -2.71, p<0.05); PM10 (z = -2.11, p<0.05); PM2.5 (z = -2.35, p<0.05), meanwhile for UFP (z = 4.72, p<0.001) and THI value (z = -4.57, p<0.001), new building was significantly higher compared to old building. There was significant association between the prevalence of SBS and the indoor air pollutants in the old building namely CO2 (OR = 3.56, 95% CI = 1.327-9.548); CO (OR = 4.95, 95% CI = 1.740-14.127); TVOC (OR = 4.71, 95% CI = 1.571-14.151); PM10 (OR = 6.23, 95% CI = 2.278-17.065) and PM2.5 (OR = 4.18, 95% CI = 1.564-11.199), while in the new building, the prevalence of SBS showed significant association with an indoor air pollutant namely UFP (OR = 6.53, 95% CI = 1.757-24.327). After controlling the cofounders; age, medical condition, smoking and having pet at home, the results showed that CO2, CO, TVOC, PM10, PM2.5 influenced SBS in old building while UFP influenced SBS in the new building. This study suggested that when there was an increase in the ventilation rates per person in office building, it would significantly reduced prevalence of SBS, even though both buildings meet the existing ASHRAE ventilation standards for office building. Reduction in prevalence of SBS would depend on the increase in ventilation rates, ventilation effectiveness and reduction in indoor air pollutants that can cause SBS.